2007
DOI: 10.1177/0363546507301258
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Parameters for Assessing Risk of Recurrent Hamstring Injuries in Elite Athletes

Abstract: A history of anterior cruciate ligament injury was the only statistically significant risk factor for a recurrent hamstring strain in our study. Of the imaging parameters, the MR length of a strain had the strongest correlation association with a repeat hamstring strain and therefore may assist in identifying which athletes are more likely to suffer further reinjury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(198 citation statements)
references
References 24 publications
8
185
1
4
Order By: Relevance
“…Our finding that most hamstring injuries affected the biceps femoris muscle was consistent with previous studies in Australian football (Connell, et al, 2004;Koulouris, Connell, Brukner, & Schneider-Kolsky, 2007). Furthermore, in accordance with the findings of Slavotinek et al (Slavotinek, Verrall, & Fon, 2002), we found no relationship between the specific muscle involved and the lay-off time.…”
Section: The Majority Of Hamstring Injuries Affect the Biceps Femorissupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that most hamstring injuries affected the biceps femoris muscle was consistent with previous studies in Australian football (Connell, et al, 2004;Koulouris, Connell, Brukner, & Schneider-Kolsky, 2007). Furthermore, in accordance with the findings of Slavotinek et al (Slavotinek, Verrall, & Fon, 2002), we found no relationship between the specific muscle involved and the lay-off time.…”
Section: The Majority Of Hamstring Injuries Affect the Biceps Femorissupporting
confidence: 93%
“…It is possible that these cases involve subtle muscle injury that is below the sensitivity of MRI detection (Verrall, Kalairajah, Slavotinek, & Spriggins, 2006). Another possibility is that players could have an alternative diagnosis, such as back-related problems, neural tension, or muscle spasm (Connell, et al, 2004;Koulouris, et al, 2007;Müller-Wohlfahrt, Ueblacker, & Hänsel, 2013;Müller-Wohlfahrt, Ueblacker, & Hänsel, 2010).…”
Section: Mri Grading Of Thigh Muscle Injuries Relates To Lay-off Timementioning
confidence: 99%
“…This, together with the capability to evaluate multiple anatomic planes, make it the most suitable technique to evaluate muscle injures [23][24][25][26]. Most muscle injuries might not require imaging, but as this noninvasive technology continues to improve and becomes even more commonplace, it can play a role in rehabilitation planning and prognosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is more accurate in the assessment of acute hamstring injuries than most other imaging modalities (Connell et al 2004;Verrall et al 2006;Koulouris et al 2007;Askling et al 2013a). It has the ability to diagnose hamstring pathology, such as subtle tendinosis (tendinopathy), tears and low-grade bursitis for the purposes of guiding rehabilitation and possible radiologically guided intervention (Verrall et al 2006;Askling et al 2013a).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%